2013
DOI: 10.1021/nl304741t
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Molecule to Solid State: Reactivity of Supported Metal Clusters

Abstract: The evolution of the adsorption energy of carbon monoxide (CO) molecules on palladium (Pd) clusters as function of Pd particle size from the molecular regime (less than ~100 atoms per particle) to the bulk regime has been revealed. This adsorption energy is retrieved from the residence time of CO molecules on the Pd clusters, measured by a pulsed molecular beam technique, versus temperature. Unprecedented accuracy on the determination of the particle size has been achieved here by using a regular array of meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
100
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(102 citation statements)
references
References 54 publications
2
100
0
Order By: Relevance
“…For largest particle size (3.5 nm=∼3848 atoms), the adsorption energy is of the order of 31.07 kcal mol -1 . This value is very close to the bulk Pd expected value (33.03 kcal mol -1 ) [18]. In an experimental study it is reported that the CO oxidation depends on the particle size, where Pd n (n≤6) are more reactive than larger clusters [20].…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…For largest particle size (3.5 nm=∼3848 atoms), the adsorption energy is of the order of 31.07 kcal mol -1 . This value is very close to the bulk Pd expected value (33.03 kcal mol -1 ) [18]. In an experimental study it is reported that the CO oxidation depends on the particle size, where Pd n (n≤6) are more reactive than larger clusters [20].…”
Section: Introductionsupporting
confidence: 85%
“…For instance, the CO adsorption energy depends on the Pd cluster size [18,19]. For 4.7±2 atoms clusters, the CO adsorption energy is 21.08 kcal mol -1 and the CO chemisorption presents strongly irregular variation up to 1.8 nm (∼142 atoms) with energies of 5.98 kcal mol -1 .…”
Section: Introductionmentioning
confidence: 99%
“…In many fundamental research fields, notably in surface science [1], they serve as model templates and atomically controlled spacers, for the manipulation and study of nanoparticles [2][3][4], molecules [5][6][7][8][9][10], or single atoms [11]. Most of the time, chemical stability of insulating thin films upon charged particle irradiation is required, e.g., for characterization using electron spectroscopy and microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated number of exposed Pd atoms was calculated by using a simple hemisphere model for the cluster shape, a shape identified experimentally for similar-sized Pd clusters in a CO-containing atmosphere. [55] In brief, the surface atoms form a hemispherical shell of thickness of one Pd atom (d ¼ 0.27 nm). The shell outer radius is the cluster radius (R), assuming the bulk Pd density (considering this to be the reality), and its inner radius is (R À d).…”
Section: Resultsmentioning
confidence: 99%